Artificial intelligence, truth and wisdom: A Franciscan perspective - Martín Carbajo-Núñez OFM (Warszawskie Studia Teologiczne)
This article delves into how to live in truth and attain wisdom in the age of Artificial Intelligence (AI), using the Franciscan Tradition as a guide and reference. While AI can help expand our knowledge, it also blurs the line between truth and falsehood (1st part). The second part, drawing on Socrates' reflections on writing, explores the evolving concept of wisdom in the context of AI. The third part examines how the Franciscan Tradition has approached truth and wisdom. It is concluded that the Franciscan holistic and relational perspective can guide the development of AI towards creating a more humane and fraternal world.